Pengaruh Optimalisasi Pengelolaan Transaksi Finansial Terhadap Pencapaian Penerimaan Pendapatan Yang Dimediasi oleh Fee Based Income Brilink - Simatupang, De Vilera; Syarief, Rizal; Gustari , Irvandi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
In recent years, the banking industry has experienced major challenges, namely unstable interest income. Banks need to consider alternative income outside of interest income. If the bank wants to maintain its profit level, the sources of income other than income from loan interest must be intensified through fee-based income. This study aims to determine the number of agents, CASA, jawara juragan agents, and BEP agents affecting BRILink financial transactions, financial transactions affecting BRILink fee-based income, and the implications of income receipts affected by BRILink fee-based income. This study uses secondary data with CASA variables, number of agents, jawara juragan agents, BEP agents, financial transactions, fee-based income (FBI), and income receipts. Data were analyzed using Structural Equation Modeling (SEM), which was processed through Smart PLS 4.0. The results showed that from the CASA variables, the number of agents, jawara juragan agents, and the BEP agents, only the number of agents significantly influenced BRILink financial transactions. BRILink's financial transactions significantly affect BRILink's fee-based income. BRILink's fee-based income has a significant influence on income receipts.